LA REPRESENTACIÓN MEDIÁTICA DE LOS MIGRANTES VENEZOLANOS EN EL ECUADOR. EL RELATO, LAS PERCEPCIONES Y EL ROL SOCIAL DE LOS MEDIOS DE COMUNICACIÓN - CEREZO CASTRO LIMBERT JUSSEBBE (2024)
The study aims to examine how stories, perceptions and the media influence the media representation of the Venezuelan migrant. Since the way in which these are portrayed can reinforce stereotypes and prejudices, we also seek to analyze how these influence public opinion and policies towards this group. To achieve these objectives, a descriptive and explanatory research was used under a non-experimental design. In this aspect, the qualitative method was used to obtain a better understanding of the variables. To comply with these proposals, the digital media of Ecuador was taken as the population, in which El Comercio, El Universo and el Telégrafo were selected as a sample to obtain the necessary information. The work also has a documentary analysis and observation techniques, which are prepared through a review of the literature, observation sheets and a comparative table, the latter are carried out on the aforementioned newspapers to observe the level of coverage and objectivity they manage on the immigration issue.